A longitudinal examination of elite youth soccer players: The role of passion and basic need satisfaction in athletes' optimal functioning. (November 2018) - Verner-Filion, Jérémie; Vallerand, Robert J.
Abstract: Objectives: Grounded in the basic psychological needs theory (BPNT; Ryan & Deci, 2017) and dualistic model of passion (DMP; Vallerand et al., 2003), the aim of the present study was to examine within-person variations in athletes' optimal functioning (i.e., positive and negative affect, athletic satisfaction, and quality of preparation and performance) as a function of passion types and need satisfaction over the course of three competitive seasons. Method: Elite youth soccer players (n = 91) completed multi-section questionnaires on up to five occasions over the course of three competitive seasons. Results: Results of Hierarchical Linear Modeling analyses showed that between-person variations in harmonious passion (HP) were positively related to optimal functioning, whereas it was only partially the case with obsessive passion (OP). Moreover, within-person variations in the satisfaction of autonomy, relatedness, and competence were also associated with increases in athletes' psychological well-being (i.e., positive and negative affect, and athletic satisfaction). Additionally, results from a multilevel indirect effects model revealed that HP and increases in competence were both positively related to increases in the quality of athletes' preparation, which in turn led to increases in performance, as rated by coaches, over the span of three competitive seasons. Conclusions: Overall, the results offer support for the effects of needs and passion on optimal functioning and are discussed in line with their implications for athletes in elite youth sports settings. Highlights: The role of passion and basic needs on the optimal functioning of soccer players is examined. This study relied on a three-year, multi-wave study with soccer players from a professional academy. Results of HLM analyses showed the effects of passion in changes in the optimal functioning of athletes. Increases in all three needs positively influenced changes in the well-being of athletes. Harmonious passion and changes in competence increased the quality of preparation, which led to increases in performance.